Circulating blood cells influence the fibrinolytic capacity of clots generated in the presence of detergent sclerosants. (May 2020) - Li, Tom; Connor, David; Parsi, Kurosh
Objectives: To investigate the effects of sodium tetradecyl sulphate and polidocanol on fibrinolytic potential of sclerosant-incubated clots. Methods: Serial dilutions of sodium tetradecyl sulphate and polidocanol were incubated with platelet poor plasma and whole blood samples. Rotational thromboelastometry was used to determine the lysis of sclerosant-incubated clots in whole blood. Fibrin generation and fibrinolysis were quantified using an overall haemostatic potential assay on platelet poor plasma. Results: Rotational thromboelastometry analysis of whole blood revealed increased maximum lysis in the presence of sodium tetradecyl sulphate but decreased maximum lysis at low concentrations of polidocanol. Clots generated using platelet poor plasma in the overall haemostatic potential assay demonstrated no significant change in fibrinolysis for both sclerosants at all concentrations measured. Discussion: Sodium tetradecyl sulphate and polidocanol produce differing effects on the fibrinolytic potential depending on sample type and concentration. In whole blood, sodium tetradecyl sulphate produces clots more sensitive to lysis while polidocanol produced fibrinolytic-resistant clots.